Origin of the enhancement in transport properties on polycrystalline SnSe with compositing two-dimensional material MoSe2. (7th February 2017) - Huang, Xue-Qin; Chen, Yue-Xing; Yin, Meijie; Dan Feng,; He, Jiaqing
Abstract: P -type SnSe compositing with 2D MoSe2 materials have been prepared by the solid solution method followed by the spark plasma sintering technique. The total thermal conductivities of SnSe/MoSe2 composites were found to be higher than for pristineSnSe at room temperature; and the disparity between them becomes smaller at higher temperatures, where the low thermal conductivities remained. Both the carrier concentration and the carrier mobility were significantly improved after MoSe2 was introduced into the SnSe matrix along the direction perpendicular to the pressing direction, leading to an extraordinary enhancement in electrical transport performance. The maximum ZT of 0.5 was obtained at 773 K for SnSe + 1.5%MoSe2 along the direction perpendicular to the pressing direction; this value is 1.5 times as large as that of the pristine SnSe.